Essai et fiction : à propos de Hieroglyphics, a Note upon Ecstasy in Literature (Arthur Machen, 1902) - Sophie Mantrant (Cahiers Victoriens et Edouardiens)
When mentioned at all, Hieroglyphics is usually described as an essay in which Arthur Machen exposes his views on literature. The aim of this paper is to show how the “Prefatory Note”, a sort of frame narrative, blurs the borderline between essay and fiction and makes the status of the text problematic. In this preliminary text, a narrator bearing the initials “A. M.” explains that he spent long hours listening to a scholarly hermit whose views on literature he later put down on paper. Machen thus encourages the reader to identify him not as the enunciator but as the listener ; he dissociates himself from the essayist, even though the latter expresses ideas that are also his. This is part of a game of masks that is played on several textual levels.